Screening for latent acute intermittent porphyria: the value of measuring both leucocyte delta-aminolaevulinic acid synthase and erythrocyte uroporphyrinogen-1-synthase activities. - McColl, K E (1982)
Acute intermittent porphyria (AIP) is an autosomal dominantly inherited disorder of haem biosynthesis characterised by reduced activity of the enzyme uroporphyrinogen-1-(URO) synthase and compensatory increased activity of the rate controlling enzyme delta-aminolaevulinic acid (ALA) synthase. Subjects with the disorder should be identified as they are at risk of developing severe porphyric attacks if exposed to a variety of drugs or chemicals. We have assessed the value of measuring the activities of ALA synthase and URO synthase in peripheral blood cells as a means of identifying latent cases in affected families. In AIP subjects, ALA synthase activity was increased and URO synthase decreased compared to controls, through there was considerable overlap between the two groups when either enzyme was examined alone. When both enzymes were examined together, all but one of the 19 AIP patients had both increased ALA synthase activity (greater than 250 nmol ALA/g protein/h) and reduced URO synthase activity (less than 25.1 nmol URO/l RBC/h), whereas none of the 62 controls showed this enzyme pattern. Examination of 35 asymptomatic first degree blood relatives of AIP patients showed that 17 (49%) had the porphyric enzyme pattern with no sex bias. The combined study of these two enzymes permits accurate detection of latent cases of AIP and confirms its autosomal dominant inheritance.